2021
DOI: 10.1111/aor.14133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsatility on shear‐induced extensional behavior of Von Willebrand factor

Abstract: Background: Patients with continuous flow ventricular assist devices (CF-VADs) are at high risk for non-surgical bleeding, speculated to associate with the loss of pulsatility following CF-VAD placement. It has been hypothesized that continuous shear stress causes elongation and increased enzymatic degradation of von Willebrand Factor (vWF), a key player in thrombus formation at sites of vascular damage. However, the role of loss of pulsatility on the unravelling behavior of vWF has not been widely explored.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…The magnitude of VWF degradation has been shown modulated by the pulsatility of the CF‐LVAD, generating the hypothesis of pulsatility preservation as a new target to improve clinical outcomes of patients. The role of pulsatility has been an ongoing discussion as maintenance of a certain level of pulsatility contributes toward decreased GIB incidence 22–25,78–80 . Further longitudinal studies possibly using artificial intelligence algorithms are needed for better risk stratification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The magnitude of VWF degradation has been shown modulated by the pulsatility of the CF‐LVAD, generating the hypothesis of pulsatility preservation as a new target to improve clinical outcomes of patients. The role of pulsatility has been an ongoing discussion as maintenance of a certain level of pulsatility contributes toward decreased GIB incidence 22–25,78–80 . Further longitudinal studies possibly using artificial intelligence algorithms are needed for better risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…The role of pulsatility has been an ongoing discussion as maintenance of a certain level of pulsatility contributes toward decreased GIB incidence. [22][23][24][25][78][79][80] Further longitudinal studies possibly using artificial intelligence algorithms are needed for better risk stratification. This review summarizes the most recent literature and differs from existing reviews and systematic reviews in that it is focused on the overall management with a suggested algorithm which includes pump speed adjustments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VWF deficiency in the context of CF-LVAD occurs either through pump shear-induced VWF activation with subsequent exposure of the ADAMTS-13 cleavage site for enzymatic degradation or by shear stress-induced fragmentation of VWF into dysfunctional small fragments, independent of ADAMTS-13 [ 4 , 31 , 32 , 33 , 34 ]. The net effect of decreased production and increased degradation of VWF culminates in diminished VWF-dependent platelet aggregation.…”
Section: Impact Of Cf-lvad On Gastrointestinal Vasculature and Gibmentioning
confidence: 99%